Peran Islam dalam Membangun Advokasi Anti Kekerasan terhadap Perempuan di Indonesia - Susanti, Christin Amelia; Tampake, Tony; Lauterboom, Mariska (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
Violence against women is a global issue experienced by every country, including Indonesia. Aspects that are considered dominant and strong in society are needed in order to build equality, one of which is the religious aspect. In particular, Islam supports women. Through this article, we want to examine the role of Islam in efforts to build advocacy for women in Indonesia. This research uses a qualitative library research approach, by describing the reality of the Islamic religion to build advocacy for women in Indonesia. Collecting primary and secondary data through relevant literature based on the topic of the writing. The theory used to analyze is subaltern theory by Gayatri Chakravorty Spivak. The main argument is that the Islamic religion seeks to advocate anti-violence against women based on human values in Islam. The findings from this paper confirm that the Islamic religion highlights two factors that influence violence against women, namely cultural values and religious teachings. The Islamic religion in the modern context and through the Islamic feminism movement seeks to advocate and oppose violence against women.